Administrative Innovation Of The Deans Of Colleges In Baghdad Governorate - et. al., Yahya Allawi Majeed (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to identify the administrative innovation of the deans of the colleges in Baghdad governorate. To achieve the objectives of this research, we built the administrative innovation scale, which consisted of four main domains and (43) final items. The research sample totalled (304) of collaborators, i.e., deputy deans and heads of scientific departments. A set of appropriate statistical methods (SPSS) have been used for data processing. These include: T-test for two independent samples, a T-test for one sample, Pearson Correlation Coefficient, Alpha-Cronbach equation, measures of central tendency, measures of dispersion. Results revealed that the deans of the colleges of the universities in Baghdad province possess good administrative innovation and keep pace with the developments of the time.